Pengaruh Penggunaan Peta Pikiran untuk Meningkatkan Kemampuan Berbicara Argumentatif Siswa Kelas IX SMP Negeri 1 Jeruklegi Kabupaten Cilacap Tahun 2025 - Ratino Ratino; Eko Suroso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the effect of using concept maps on the speaking ability of grade IX students of SMP Negeri 1 Jeruklegi in 2025. The background of this study is the ability to convey understanding orally, especially the gap between formal and non-formal speaking. Therefore, a way is needed to overcome this, one of which is by using concept maps. Using concept maps, students can see the relationship between concepts visually so that students can easily understand and remember information more precisely. This can improve students' ability to explain material systematically and logically. The method used is an experiment with two groups, namely the experimental group that was given treatment using concept maps and the control group that did not receive learning with concept maps. The instrument used was an oral speaking test before and after treatment. The results of the data analysis showed a significant difference between the experimental group and the control group, which indicates that the use of concept maps has a positive effect on students' speaking skills. These findings recommend the use of concept maps as an alternative to varied and enjoyable speaking learning.